La didactique professionnelle : une alternative aux approches de « cognition située » et « cognitiviste » en psychologie des acquisitions - Janine Rogalski (Activités)
The paper aims at presenting professional didactics as a theoretical framework which enables a) to take into account the various components of professional competence (work process knowledge, schemes of action, « quality » of perception and motor action, concerning the whole world of action: objects, tools, social organisation and self); b) to analyse the multi-fold determinants in the development of competences, including those emphasised by the situated cognition tenants and c) to discuss the design of training situations. The evolution of situated cognition is briefly recalled, from the « strong form » as a reaction to strict cognitivism to the pre-sent « weak form(s) ». Cognitive psychology is presented in a counter-point, as departing from the initial « strong model » of human cognition as a system of information processing to proposals articulating cognition, perception, action and emotion. Situated learning is then discussed from the initial case of « everyday » mathematics in relation with the evolutions of the cognitivist theories of learning. Finally, the theoretical project of professional didactics is developed: It is shown how professional didactics integrates the theory of activity (with the model of twofold regulation) and the main didactical concepts (knowledge of reference, conceptualisation and schemes of action, didactical transposition of work situations), and proposes an integrative and systemic model for studying development of professional competence and training.